Evaluation of the Problem of Universals in the Medieval Age with Aristotelian Realism - Kar, Erman (Fırat University, 2026)
The question of whether universals have an exact reality is one of the most important problems in the history of medieval philosophy. During the Middle Ages, this problem was analysed by the ecoles. Realism defines that universals are entities that precede physical bodies, i.e. particular entities, and they transcend them. Nominalist doctrine, on the other hand, claims that universal concepts consist of words or sounds expressing the commonality and similarity of particulars. The approach that creates a new alternative to both opposing views and brings an important analysis of the status of universals in Scholastic doctrine is called Aristotelian realism. According to this approach, universals co-exist with particulars and universals are immanent to them. The aim of this study is to examine the foundations of the philosophers' questioning about the nature of universals through Aristotle's realism. Firstly, the question of what is the universal, which is the object of reason, and whether universal concepts have objective realities will be analyzed through the conceptual terminology of the problem of universals. Secondly, the emerging ecoles on the problem of universals in medieval thought, realism, Aristotelian realism and nominalism will be discussed. Finally, the approaches of medieval philosophers to the question of whether universals have an exact existence will be examined from the perspective of Aristotelian realism, and in this context, the effects of Aristotelian teaching on medieval philosophy will be evaluated.

Tümel kavramların nesnel bir gerçekliği var mıdır? sorusu Orta Çağ felsefe tarihinin en önemli problemlerinden birisidir. Orta Çağ boyunca ekoller tarafından söz konusu problem irdelenmiştir. Realizm; tümelleri, tekil varlıklardan önce gelen onları aşan varlıklar olarak tanımlar. Nominalist öğreti ise tümel kavramların tekillerin ortaklıklarını ve benzerliklerini ifade eden sözcüklerden ya da seslerden ibaret olduğunu iddia eder. Her iki karşıt görüşe yeni bir alternatif oluşturan ve Skolastik öğretide tümellerin statüsüne dair önemli bir analiz getiren yaklaşım ise Aristotelesçi realizm olarak adlandırılır. Bu yaklaşıma göre tümeller, tekillere içkin olarak, onlarla birlikte vardırlar. Bu çalışmanın amacı filozofların tümellerin mahiyetine dair yaptıkları sorgulamanın temellerini Aristoteles’in realist öğretisi üzerinden incelemektir. İlk olarak; aklın nesnesi olan tümelin neliği ve tümel kavramların nesnel gerçeklikleri var mıdır sorusu tümeller sorununun kavramsal terminolojisi başlığı üzerinden analiz edilecektir. İkinci olarak Orta Çağ düşüncesinde tümeller sorununa dair ortaya çıkan ekoller; realizm, ılımlı realizm ve nominalizm tartışılacaktır. Son olarak Orta Çağ filozoflarının, tümellerin nesnel bir karşılığı olup olmadığına dair getirdikleri yaklaşımlar Aristotelesçi realizm perspektifinde incelenecektir ve bu bağlamda Aristotelesçi öğretinin Orta Çağ felsefesine katkıları değerlendirilecektir.
Aristotelesçi Realizm ile Orta Çağ'da Tümeller Sorununun Değerlendirilmesi
Keywords: Medieval Philosophy; Ortaçağ Felsefesi; History of Philosophy (Other); Felsefe Tarihi (Diğer)